1984
DOI: 10.1002/pssb.2221230103
|View full text |Cite
|
Sign up to set email alerts
|

Successive Phase Transitions in (NH4)3H(SO4)2 and (ND4)3D(SO4)2 Crystals Studied by EPR of the VO2+ Ion and SeO Radical

Abstract: The successive phase transitions of (NH,),H(SO,), crystal and its deuterized analog are studied from 90 to 420 K using V02+ ion and the SeOT radical as EPR probes. On the basis of EPR experiments with ferroelastic domain switching in phase 11, a new model of the VO2+ complex in the crystal is proposed, with V02+ occupying an NHt (I) vacancy and able, a t high temperatures, to reorient very extensively coordinating in three ways with four of the nearest six oxygen atoms. Gradual hinderin of NHI reorientation wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 21 publications
3
6
0
Order By: Relevance
“…Similar coordination of VO 2+ ion in (NH 4 ) 3 H(SO 4 ) 2 crystal was determined by Minge and Waplak [13].…”
Section: +supporting
confidence: 80%
“…Similar coordination of VO 2+ ion in (NH 4 ) 3 H(SO 4 ) 2 crystal was determined by Minge and Waplak [13].…”
Section: +supporting
confidence: 80%
“…(1) and Eqs. (2)- (4) The EPR spectum of single-domain crystal shows at RT two types of complexes, denoted as Mn2 +(1) and Mn 2 +(2), similarly as it has been found for VO 2 + ions doped (NH4 )3 Η(SO4) 2 monocrystals [8][9][10]. Only one complex of Mn 2 + has been described in paper [5].…”
Section: Methodsmentioning
confidence: 63%
“…The earlier EPR data driven from VO 2 + and SeO3-paramagnetic centers in (ΝΗ4)3Η(SO4 ) 2 [9,10] show the successive unit cell doubling recorded at phase transitions. These data are fully reproducible in Mn 2 + spectra as well.…”
Section: Discussionmentioning
confidence: 88%
“…The phase transitions in TAHS studied by E P R o f VO?' and SeO; has been reported by Minge and Waplak (1984). EPR studies of the phase transitions in TAHS using Cu" and Mn2' as probes have been reported by Babu et ai (1985).…”
Section: Wu Ching-jiun Et Aimentioning
confidence: 83%